Effect of some physical parameters and crospovidone on directly compressed frusemide tablets - Chaulang, Ganesh Mahadev; Patil, Kundan Suresh; Ghodke, Dhananjay Sahebrao; Yeole, Pramod Govindrao; Bhosale, Ashok Vitthal; Hardikar, Sharwaree Rajan (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of this study was to evaluate the effect of increasing crospovidone (superdisintegrant) load on the characteristics of fast-disintegrating tablets for the potential use of the drug for its therapeutic effect. Five tablet formulations, F0, F1, F3, F7, and F10 containing 0%, 1%, 3%, 7%, and 10% (w/w) of crospovidone, respectively, frusemide and microcrystalline cellulose (PH102), were prepared by direct compression, at a different compression forces.Tablet weight variation, content uniformity, crushing strength, disintegration time, wetting time, and in vitro release were measured for each formulation at each compression force. A linear increase in compression force resulted in an exponential increase in hardness for all formulations, a linear increase in disintegration and wetting times was observed for the formulations F0, F1, F3 with the increase in compression force.The tablet formulation F7 indicated, there was no effect of compression force on disintegration and wetting time. The in vitro release of the drug was increased with increase in concentration of crospovidone irrespective the compression force. However, storage under high humidity conditions caused the softening of the tablets containing the high amount of crospovidone, leading to softening of tablets. Fast disintegration of the tablets within 1-2 min is prerequisite for improving the dissolution of frusemide, attributed to increase in speed at which maximum surface area of sparingly soluble drug is exposed to the dissolution medium. However, tablet containing high amount of crospovidone must beprotected from the atmospheric moisture because storage of these tablets at high humidity led to softening and losing the tablet characteristics.